2015
DOI: 10.1007/s00381-015-2705-7
|View full text |Cite
|
Sign up to set email alerts
|

Increased cerebrospinal fluid cleaved tau protein (C-tau) levels suggest axonal damage in pediatric patients with brain tumors

Abstract: Cerebrospinal fluid cleaved tau levels in children with newly diagnosed brain tumors exhibit markedly elevated cerebrospinal fluid cleaved tau levels, suggesting axonal damage. This axonal injury does not seem to correlate with lipid peroxidation at least when as assessed by cerebrospinal fluid 9-hydroxyoctadecadienoic acid levels. There was no association found between the biomarkers and multiple independent variables obtained at pre- and post-tumor resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…However, CSF was not analyzed in that study. It should be noted that alterations in HODE levels are not restricted to MS. As for reports on HODE levels in CSF in other neurological diseases, 9-HODE levels in children with brain tumors 22 and hydrocephalus 23 did not differ from controls. Outside the central nervous system, HODEs have been implicated in various contexts, e.g.…”
Section: Discussionsupporting
confidence: 56%
“…However, CSF was not analyzed in that study. It should be noted that alterations in HODE levels are not restricted to MS. As for reports on HODE levels in CSF in other neurological diseases, 9-HODE levels in children with brain tumors 22 and hydrocephalus 23 did not differ from controls. Outside the central nervous system, HODEs have been implicated in various contexts, e.g.…”
Section: Discussionsupporting
confidence: 56%
“…To our knowledge, this is the first report of such a correlation between Tau serum level and the presence of a brain tumor. So far, only one report has been published of an association between the levels of Tau in CSF and brain tumors in pediatric patients [36, 45], while several reports of correlations with Tau have been published for other non-neurodegenerative disorders, including traumatic brain injury (TBI) [34, 33] and stroke [46]. In TBI, the serum level of Tau was associated with the presence of macroscopic lesions detectable on brain imaging, and with the patients’ clinical outcome [33].…”
Section: Discussionmentioning
confidence: 99%
“…74) A prospective clinical observational study demonstrated that children with newly diagnosed brain tumors exhibit markedly elevated CSF cleaved tau levels, which were suggestive of axonal damage. 76) Prostaglandin D2 synthase (PGD2S) levels were six-fold lower in the pediatric tumor samples versus control samples in study by Rajagopal et al 77) The authors speculated that the reduction is a host response to the presence of the tumor. 77) PGD2S is a glycoprotein that is abundant in the CSF and is synthesized and secreted by both glial cells and the choroid plexus.…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…They reported that the 3-methoxy-4-hydroxyphenylglycol level of the CSF was significantly higher in pediatric patients with astrocytoma than in those with medulloblastoma [ 74 ]. A prospective clinical observational study demonstrated that children with newly diagnosed brain tumors exhibit markedly elevated CSF cleaved tau levels, which were suggestive of axonal damage [ 76 ].…”
Section: Csf Biomarkers Of Pediatric Neurological Disordersmentioning
confidence: 99%